1999
DOI: 10.1042/bj3420143
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate inhibits the first committed step of purine biosynthesis in mitogen-stimulated human T-lymphocytes: a metabolic basis for efficacy in rheumatoid arthritis?

Abstract: The immunosuppressive and anti-inflammatory effects of low-dose methotrexate (MTX) have been related directly to inhibition of folate-dependent enzymes by polyglutamated derivatives, or indirectly to adenosine release and/or apoptosis and clonal deletion of activated peripheral blood lymphocytes in S-phase. In this study of phytohaemagglutinin-stimulated primary human T-lymphocytes we show that MTX (20 nM to 20 microM) was cytostatic not cytotoxic, halting proliferation at G(1). This stasis of blastogenesis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 41 publications
1
51
0
2
Order By: Relevance
“…As expected, only guanosine prevented the inhibitory effect of MPA and only thymidine allowed cell division to proceed in 5FU-treated cells. The two major targets of MTX are dihydrofolate reductase and TS but at low concentrations (20 nM-0.2 M); MTX was also shown to block the first committed step of purine biosynthesis (17). Therefore, we determined whether blockade of either one of the two biosynthesis pathways, purine or pyrimidine synthesis, could account for MTX-induced inhibition of cellular divisions.…”
Section: Blockade Of Nucleotide Synthesis Inhibits Proliferation Of Pmentioning
confidence: 99%
“…As expected, only guanosine prevented the inhibitory effect of MPA and only thymidine allowed cell division to proceed in 5FU-treated cells. The two major targets of MTX are dihydrofolate reductase and TS but at low concentrations (20 nM-0.2 M); MTX was also shown to block the first committed step of purine biosynthesis (17). Therefore, we determined whether blockade of either one of the two biosynthesis pathways, purine or pyrimidine synthesis, could account for MTX-induced inhibition of cellular divisions.…”
Section: Blockade Of Nucleotide Synthesis Inhibits Proliferation Of Pmentioning
confidence: 99%
“…The antiproliferative effect of mycophenolate acid on T cells was clearly demonstrated in vitro (7,8,12,13). Methotrexate (MTX) is a folate antagonist that blocks dihydrofolate reductase and TS (14), but it can also block the first step of purine biosynthesis (15). We have previously shown that in primary T cells, MTX inhibits T cell division by specifically depleting thymidine nucleotides (8,16).…”
Section: Restriction Of De Novo Nucleotide Biosynthesis Interferes Wimentioning
confidence: 99%
“…The mechanism by which MTX mediates its immunosuppressive and an anti-inflammatory effects is still elusive. Apoptosis and clonal deletion of activated peripheral T cells (10), suppression of purine biosynthesis in mitogen-stimulated T cells (11), down-regulation of inflammatory cytokines (12)(13)(14), adenosine release (15,16), modulation of release of metalloproteases, and expression of cell surface adhesion molecules (17) have been used to explain the effects of MTX in RA.…”
mentioning
confidence: 99%